2018
DOI: 10.1099/ijsem.0.002962
|View full text |Cite
|
Sign up to set email alerts
|

Penicillium tunisiense sp. nov., a novel species of Penicillium section Ramosa discovered from Tunisian orchard apples

Abstract: Two similar Penicillium isolates could not be identified as previously described species in a survey of orchard apples from Tunisia for patulin-producing fungi. These isolates are described as novel species using multilocus DNA sequence analysis of partial β-tubulin, calmodulin and nuclear ribosomal internal transcribed spacer regions; and morphological, physiological and biochemical characteristics. The isolates were considered negative for patulin production since the IDH gene fragment was not detected and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…10) at 118 days, it was found that the fungal development remained low. Previous studies with different micro additives showed that there was significantly improvement of the antifungal properties of mortars [22,31] but this fact could only be observed in the sample B1 2% cork .…”
Section: Accelerated Fungal Growthmentioning
confidence: 83%
See 1 more Smart Citation
“…10) at 118 days, it was found that the fungal development remained low. Previous studies with different micro additives showed that there was significantly improvement of the antifungal properties of mortars [22,31] but this fact could only be observed in the sample B1 2% cork .…”
Section: Accelerated Fungal Growthmentioning
confidence: 83%
“…DNA extraction was performed using a ''FastDNA Ò SPIN Kit" (MP Biomedicals, Santa Ana, USA) according to the manufacturer's handbook. Gene amplification of beta tubulin gene (BenA) was performed using the method described in Ouhibi et al [22]. The fungal isolate chosen to perform the antifungal assay was deposited in Micoteca da Universidade do Minho (MUM) culture collection with the unique number strain MUM 19.43.…”
Section: Fungal Isolation and Identificationmentioning
confidence: 99%
“…Penicillium species in this section are characterized by biverticillate or terverticillate conidiophores [1]. They are commonly isolated from soil [67,68], but it is also found in sea water, fruiting bodies of Chroogomphus rutilus, and Tunisian orchard apples [69][70][71]. P. scabrosum has been reported to produce cyclopenin, cyclopenol, viridicatin, fumagillin, as well as a large number of unknown metabolites [67].…”
Section: Discussionmentioning
confidence: 99%
“…Wet mounts were prepared by staining the fungal samples with lactophenol cotton blue (Merck) and the slides were examined under light optical microscope using a Leica DM5000B apparatus to describe and measure micro-morphological characteristics. Samples were prepared for scanning electron microscopy according to [27] and were added to aluminium pin stubs with electrically conductive carbon adhesive tape (PELCO Tabs) on a Phenom Standard Sample Holder (SH) at 5 or 10 Kv and a spot size of 3.3. The samples were 10 Angstrom Au coated.…”
Section: Morphological Characterizationmentioning
confidence: 99%